Socio-spatial fragmentation and contemporary urbanization - Sposito, Maria Encarnacao Beltrao [UNESP] (Univ Nacl Centro Provincia Buenos Aires, Centro Investigaciones Geografica, 2024)
Sociospatial fragmentation is addressed in this text as an analytical perspective to understand contemporary urbanization. We associate it with the theory of the Production of Urban Space (Lefebvre, 1974), valuing the ideas of Political Economy of Urbanization (Singer, 1973) and Political Economy of the City (Santos, 1994), but simultaneously we have the interest of contribute to the understanding of the dynamics that, in the last two or three decades, have guided an important set of transformations, especially in Latin American cities. When we refer to contemporary urbanization, we are dealing not only with processes of a demographic or spatial nature, but also, and above all, with a social and political nuance. We live in an urban society, although part of the population still resides in the countryside. So, this process is significant to understand the current world. To develop this text, we will initially focus on some method principles. Next, we will provide elements to circumscribe the concept of socio-spatial fragmentation. In the third section, the analysis will take two Brazilian cities as reference. Finally, not exactly as conclusions, but with a view to opening the interpretation to debate, we present a synthesis, valuing the idea of complexity, announced in the title of the scientific event for which these ideas were originally organized.
Keywords: Socio-spatial fragmentation; Contemporary urbanization; Production of urban space; Urban periphery